Introducing LIR (Lithotheque Ireland), a reference collection of flaked stone tool raw materials from Ireland - Killian Driscoll; Adrian L. Burke; Graeme M. Warren (Journal of Lithic Studies, 2016)
The LIR (Lithotheque Ireland) reference collection of flaked stone tool raw materials from Ireland began in 2013, and is based on the geological prospection from two projects. The first (2013-2015) focused attention primarily on Carboniferous cherts from the northwest of Ireland, collecting 405 samples. The second (2015-2017) is currently collecting samples of the Cretaceous flint primarily from in situ contexts in the northeast of Ireland, but also includes beach surveys of Cretaceous flint from around the island; the first phase of geological prospection in Autumn 2015 collected 239 samples, with the geological prospection continuing in 2016. Therefore, to date the collection contains over 600 hand samples of chert and flint, along with a small number of other materials (siliceous limestone, tuff, mudstone). The physical reference collection is housed at the UCD School of Archaeology, University College Dublin and contains the geological hand samples along with the various thin sections of the samples that are used for petrographic analysis. The physical collection is complemented by an online database that is to be used alongside the physical collection, or can be used as a stand-alone resource. This paper provides an overview of the database’s metadata and the processes of data entry and editing, to serve as a reference point for the database and the fieldwork undertaken to date, and to serve as a template for other researchers undertaking similar work on lithic reference collections.